Windows Mobile Game Development Building games for the Windows Phone and other mobile devices - Dawes, Adam (Apress : Imprint: Apress, 2010)
This book will provide you with a comprehensive guide to developing games for both the Windows Mobile platform and the Windows Phone using the industry standard programming languages C# and VB .NET. You will be walked through every aspect of developing for the Windows Mobile platform-from setting up your development environment for the first time to creating advanced 3D graphics. Finally, you'll learn how you can make your applications available to others, whether distributing for free or selling online. Using extensive code samples throughout, you'll gather all the information needed to create your own games and distribute them successfully for others to enjoy. Aimed primarily at C# developers, almost everything in the book can be used in VB .NET too. For those areas where this is not the case, workarounds are suggested so that VB .NET developers are still able to use the techniques described.